Pure leydig cell tumour – a rare virilizing tumour in a young female - Pranav Pramod Patwardhan; Ashvini Kolhe; Rachana Chaturvedi; Amita S. Joshi (International Journal of Medical Research and Review, 2018)
Sex cord stromal cell tumours constitute 5-8% of all ovarian neoplasms of which pure leydig cell tumours constitute 0.1%. These tumours are most commonly found in the post-menopausal age group and patients present with a rapid onset of symptoms of androgen excess like hoarseness of voice, clitoromegaly and hirsutism. We present a case of 39 year old female, who presented with virilising symptoms since 2 years. Serum Testosterone levels were raised and CT revealed homogeneously enhancing mass of 2.8 cm in size in the right ovary. An unilateral oophorectomy was done and sent for histopathological examination. On Gross examination, the ovary revealed the presence of a well circumscribed greyish white tumour with multiple yellowish areas. Microscopy revealed features suggestive of pure leydig cell tumour with reinke crystals. Post operatively, the patient improved symptomatically. The unusual features seen in this case were younger age at presentation and insidious onset of symptoms. The presentation of pure leydig cell tumour- hilar type at such a young age is extremely uncommon.